Writing Hong Kong Sinophonicity : history, gender and ethnicity in Hong Kong fiction - Long, Chao (2019)
The fact that Hong Kong has a long literary tradition is often neglected in much of the public discussion about the city’s political and economic situation. The marginal place that literature occupies subsequently inspires writers to approach Hong Kong’s colonial formation in an alternative light, one that can be understood as an act of decolonization of Hong Kong’s culture. This dissertation therefore argues for a conceptualization of Sinophonicity that depicts the formation of the local Hong Kong subject as constructed in literary fiction, in order to articulate how Hong Kong literature produces decolonizing discourse and pressures. Deriving from the discourse of Sinophone studies, the term “Sinophonicity” differentiates from the monological signifier “Chineseness” by putting an emphasis on the diverse cultural practices of Sinitic language-speaking communities, including Han communities on the Chinese mainland. In unfolding its meaning, I locate three aspects that are most pertinent to articulating the relationship between Hong Kong’s colonial formation and its literature—namely, history, gender, and ethnicity. So far, no thesis written in English or Chinese within Hong Kong and beyond has adopted such a theoretical tool to analyze Hong Kong literature. Thus, my dissertation will be structured in accordance with these three aspects, in the hopes of shedding new light on the complex historical formation of Hong Kong’s Sinophone culture. Chapter one sets out with a historical inquiry into the processes of identity formation in Hong Kong from the perspective of historiography in Dung Kai-cheung’s Works and Creation: Vivid and Lifelike (2005). By analyzing Dung’s construction of a personalized history of artifacts, the chapter argues for a notion of historical Sinophonicity that questions prevailing models of identity formation in official historical discourse. Chapter two expands the purview of the historical inquiry in chapter one with its discussion of the notion of gendered Sinophonicity that is constructed in Wong Bik-wan’s Portraits of Martyred Women (1999) and Children of Darkness (2013). The chapter focuses on Wong’s construction of oral histories as a means to write against the hegemonic representations of womanhood and manhood in a Chinese cultural context. Chapter three then introduces a notion of ethnic Sinophonicity to the discussion by reading Xu Xi’s Hong Kong Rose (1997) and The Unwalled City (2001), with the aim of making the hidden problems of ethnic relations visible in Hong Kong society. Such an analysis also forms a useful comparison with the previous two chapters, thus deepening our understanding of the intersectionality of class, gender and ethnicity on identity formation. Collectively, the conceptualization of Sinophonicity in the three chapters attests to the medium of literary fiction as an effective site for producing decolonizing impetus, in order to better position Hong Kong in post-handover years.